MAML2 Gene Rearrangement Occurs in Nearly All Hidradenomas: A Reappraisal in a Series of 20 Cases. (28th November 2022) - Russell-Goldman, Eleanor; Hanna, John
Abstract: Hidradenoma is a benign cutaneous adnexal neoplasm that occurs across a wide age range and at a variety of anatomic sites. Its most characteristic morphologic feature is the presence of diverse cell types including squamoid, clear, plasmacytoid, and mucinous cells. Hidradenoma is morphologically and molecularly similar to mucoepidermoid carcinoma, and both tumors are characterized by recurrent CRTC1-MAML2 cytogenetic translocations. Previous studies have suggested that approximately half of hidradenomas possess this translocation. This finding raised the question of whether translocation-negative hidradenomas might have an alternate molecular basis. Here, we sought to reevaluate the frequency of MAML2 translocation in hidradenoma in a series of 20 cases. We find that 90% show evidence of MAML2 translocation, suggesting that this genetic event is a nearly invariant feature of hidradenoma. These results inform our molecular understanding of this tumor and may be useful in challenging cases to distinguish hidradenoma from its histologic mimics.